Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Relación entre composición y densidad de la cubierta vegetal leñosa y las características superficiales del suelo en Bosques Mixtos de Quercus del Sur de la Península Ibérica - GARCÍA, L V; POLO, A; Maltez-Moro, S; Gutiérrez, E; PÉREZ-RAMOS, I M; JORDÁN, A; MARTÍNEZ-ZAVALA, L; MARAÑÓN, T (Tendencias Actuales de la Ciencia del Suelo, 2004)
We studied the relationships between different estimates of the woody canopy density; different estimates of litter release and accumulation, and different soil properties (mainly soil reaction and macronutrient level) which have been recognised as potentially relevant for plant establishment and development in mixed Quercus forest from Natural Park “do Sudoeste Alentejano e Costa Vicentina”, Portugal (with Q. suber, Q. faginea as dominant tree species) and Natural Park “Los Alcornocales”, Spain (with Q. suber and Q. canariensis). We have found 1) A highly significant, quantitative, relationship between litter accumulation and overall canopy density. These relationships can be established either by using objective (but time-consuming) measures (by sampling or using ad hoc measuring devices) or by calibrated by-eye estimates of three simultaneous observers; 2) A significant relationship between some soil properties (N, P, ammonium) and both canopy density and litter accumulation. We conclude that these relationships are interesting in two ways: 1) They may allow to establish ‘ecotransfer functions’ for these forests (i.e. estimates o predictions about surface litter accumulation or surface values for soil properties, as organic carbon, N or P contents, by using quick field estimates of canopy density or even remote sensing estimates of canopy density), after suitable calibrations. 2) Since some soil chemical properties with known ecological relevance (e.g. C, N, P contents, soil reaction) in forest regeneration may change in a close relationship with other more studied, better known, ecological factors (light, moisture, temperature), attention should be paid to separate direct (e.g. light limitation) versus indirect (soil or litter mediated) effects of woody canopy when evaluating ecological responses at the understorey, while studying forest regeneration processes.
Keywords: acumulación de hojarasca; densidad cubierta vegetal leñosa; dosel leñoso; Quercus (voyant); suelo